Torsional shear strength and elastic properties of adhesively bonded glass-to-steel components. (July 2020) - De La Pierre, Stefano; Scalici, Tommaso; Tatarko, Peter; Valenza, Antonino; Goglio, Luca; Paolino, Davide S.; Ferraris, Monica
Abstract: Nowadays glass is widely used in building applications and coupled to steel through adhesive joining. Reliable mechanical characterization of these joints is necessary to design and predict the final structure performance. In this framework, the aim of this paper is to measure the pure shear strength and elastic modulus for design and modelling of adhesive joined glass-to-steel structures. Torsional shear strength and elastic properties of an adhesively bonded glass-to-steel component were measured on several joined steel-to-steel and steel-to-glass samples. An epoxy resin-based adhesive was used as joining material for AISI304 steel and soda-lime glass. The same steel and adhesive were used to obtain steel-to-steel joined sample bars to be tested in asymmetrical four-point bending, for comparison purposes. The indentation elastic modulus of the adhesive, both inside the joined region and as a bulk, was measured by nano-indentation and impulse excitation technique. Finally, the effect of etching on the glass was studied and correlated to the glass-steel joint strength. This study shows that torsion test can be used to provide reliable shear strength values for design and modelling glass-to-steel adhesive joined components. Graphical abstract: Unlabelled Image Highlights: Epoxy adhesive joining of soda-lime glass to AISI304 steel components Pure shear strength measurement: from small samples to full-scale structures Torsion test compared to asymmetric four-point bending Modelling the ductile-brittle behaviour of adhesive joints